The Effectiveness of Teaching Reading Skill Using QAR (Questions-Answer Relationship) Method: An Experimental Study at SMK As Salaam Sukoharjo - Noor, Aminudin, Prof. Dr. Endang Fauziati, M. Hum, Dr. M. Thoyibi, M.S (2015)
The objectives of the research are to find out: 1) whether or not the method of QAR is effective in improving students' reading skill; and 2) whether or not the method of QAR is effective in improving students' learning motivation in reading of the of Xth grade students of SMK As Salaam of Sukoharjo Academic Year of 2011/2012. The type of the research is quantitative research with descriptive comparative in nature. The design of the research is using quasi experimental design. A quasi experimental design requires at least two groups included in the study, namely a control group and an experimental group. The research was undertaken at SMK As Salaam of Sukoharjo. The subjects of the research are X grade students of SMK Assalaam Sukoharjo in Semester I academic year 2011/2012. The techniques of collecting data in the research comprises of observation, questionnaire, test, and document. The data analysis technique employed is individual t test. The research concludes that: 1) The implementation of teaching reading using QAR method in improving students reading skill and learning motivation in reading was done by questioning strategy emphasizing that a relationship exists between the question, the text, and the background of the reader. In this method, the teacher introduced students to the basic principle underlying QAR, namely generating and answering questions that are drawn on two core sources of information. These sources are the texts that students read and their background knowledge and experiences; or, in the language of QAR, information that is In the Book or In My Head, respectively. The method of QAR in teaching reading skill effective in improving students' reading skill. It is demonstrated with the post tests results that showed a significant difference in reading score averages between the control and experiment groups, with the t statistic result of -2.178 that is significant at significance level of 5%; and 2) The method of QAR in teaching reading skill effective in improving students' learning motivation in reading. It is demonstrated with the average score in learning motivation between the groups that showed a significant difference, namely the t statistic result of -4.282 that is significant at significance level of 5%. Keywords: QAR method, effectiveness, reading skill.